Argon 4s and 4p Excited States Atomic Data Applied in ARC-JET Modeling - K. Katsonis; Ch. Berenguer; A. Kaminska; M. Dudeck (International Journal of Aerospace Engineering)
Evaluated atomic data concerning the 4s and 4p configurations of Ar I are averaged in order to simplify their use in various cases of Ar plasma modeling and diagnostics. These data are used here to model a low-power arcjet, running with Argon at low pressure. In so doing, they are explicitly introduced in the chemical processes included in a fluid Navier-Stokes type code, allowing for evaluation of the spectroscopically measurable level populations and of the electronic temperatures. The characteristics of the model are described and the main processes are discussed in view of the results of the calculations.